HYDROCARBON SOURCE ROCK STUDY SOUTH SUMATRA BASIN, SOUTH SUMATRA PROVINCE BASED ON GEOCHEMISTRY DATA - Riyandhani, Cahyaningratriprima
The Western South Sumatra Extention block of South Sumatra Basin is a part of PT Medco E&P Indonesia’s operation area with main oil fields such as FRZ, SK and many others. Based on gamma ray and resistivity log analysis and also description of cutting and core from PT Medco E&P Indonesia, South Sumatra Basin consists of some formations. The three main formation analysed are Lemat Formation, Talangakar Formation and Baturaja Formation. Lemat Formation was deposited in fluviodeltaik environment with shale as a source rock. Talangakar Formation also as a source rock, was deposited in fluvial - deltaic environment, that consists of sandstone and shale intercalation with siltstone. Baturaja Formation was deposited in marine or shallow marine environtment, consists of carbonate sediments acting as a reservoir in Musi Platform area. The structural geology of the research area is represented by seismic line through wells SN – 1, RN – 1, SK – 3, FRZ – 3 and RBT deep - 1. The research area has normal faults that control the deposition of sediments and several anticlines as a result of compressional tectonic phase in Late Plio-Pleistocene. Based on geochemical analysis with alkane, sterane, and triterpane biomarker on oil samples and source rock, both of them show that oil from Musi Platform are formed by mixed organic material algal and terrestrial with fluvial - deltaic depositional environment. It shows positive correlation between oil and source rock from Lemat and Talangakar Formation and it was accumulated in the center of Musi Platform area, Western South Sumatra Extention block, South Sumatra Basin after migration process. The migration took place on stacking limestone from Baturaja Formation and also through faults on Lemat and Talangakar Formation.